Analysis of Sharia Stock Prices and Trading Volume Before and After the Announcement of Covid 19 - Ahmad Eko Saputro (Program Studi Pendidikan Ekonomi, Universitas Insan Budi Utomo, 2020)
This study analyzes the significance of the movement of sharia stocks incorporated in the Jakarta Islamic Index (JII) before and after the announcement of covid 19 in Indonesia on March 2, 2020 and analyzes the significance of trading volume on the capital market before and announced Covid 19 in Indonesia. From the analysis and discussion it can be seen that JII overcame a significant decline after the announcement of covid 19 (Sig. 2-tailed value 0,000 and a positive 1.61.84. While the trading volume increased significantly after it was announced covid 19 in Indonesia (Sig. 2- tailed amounting to 0,000 and an average of -608,745,775.0).